Avatar Assembled The Social and Technical Anatomy of Digital Bodies (PETER LANG LTD International Academic Publishers, 2017)
digital bodies; social anatomy; technical anatomy
English
Keywords: Digital Lifestyle and online world: consumer and user guides; digital bodies; social anatomy; technical anatomy